Novel Spring-Buffered Variable Valve Train for an Engine Using Magneto-Rheological Fluid Technology - Shiao, Yaojung; Kantipudi, Mahendra Babu; Jiang, Jing-Wen (Frontiers in Materials, 2019)
Vehicle manufacturers have been attempting to increase engine efficiency and decrease pollution through various methods. Variable valve actuation technology is one of these methods. Several mechanisms have been established already and have been used to develop this technology. However, these systems have common problems such as complex design, large volume, low response rate, and high-energy consumption. In this study, a novel variable valve actuation device that is compact and requires less energy was developed using magnetorheological (MR) fluid technology. The main components used in this device are an MR valve, passive buffer spring, cam, and rocker arm. This study was divided into three parts. First, an MR valve train was designed. This valve train can be constructed easily, and has fewer hydraulic and mechanical components and consumes less energy than other technologies. Second, the magnetic plate block design was optimized to obtain the required control force at optimal volume and energy. Finally, dynamical simulations pertaining to the springs and the structure were executed to analyze the dynamic condition of the valve. The simulation results indicated that the proposed MR valve could effectively provide functions of variable valve timing and variable valve lift by dynamically controlling the external current in the magnetic coil.